Flow and Mass Transfer Performance in Short Pin-Fin Channels with Different Fin Shapes - R. J. Goldstein; S. B. Chen (International Journal of Rotating Machinery)
The mass transfer (analogous to heat transfer) and pressure loss characteristics of staggered short pin-fin arrays are investigated experimentally in the range of Reynolds number 3000 to 18,000 based on fin diameter and mean approach-flow velocity. Three different shapes of fins with aspect ratio of 2 are examined: one uniform-diameter circular fin (UDCF) and two stepped-diameter circular fins (SDCF1 and SDCF2). Flow visualization using oil-lampblack reveals complex flow characteristics associated with the repeated production of horseshoe vortices and fin wakes, and the interactions among these. The SDCF1 and SDCF2 arrays show flow characteristics different from the UDCF array due to downflow from the steps. For all arrays tested, the near-endwall flow varies row by row in the initial rows until it reaches a stable pattern after the third row. The row-averaged Sherwood numbers obtained from the naphthalene sublimation experiment also show a row-by-row variation pattern similar to the flow results. While the SDCF2 array has the highest mass transfer rate, the SDCF1 array has the smallest pressure loss at the same approach-flow velocity. The fin surfaces have higher array-averaged Sherwood number than the endwall and the ratio between these changes with fin shape and Reynolds number. The performance of the pin-fin arrays is analyzed under two different constraints: the mass[heat transfer rate at fixed pumping power, and the mass/heat transfer area and pressure loss to fulfill fixed heat load at a fixed mass flow rate. In both cases, the SDCF2 array shows the best performance.